2011
DOI: 10.1103/physreve.83.046207
|View full text |Cite
|
Sign up to set email alerts
|

Delay and diversity-induced synchronization transitions in a small-world neuronal network

Abstract: The synchronized behaviors of a noisy small-world neuronal network with delay and diversity is numerically studied by calculating a synchronization measure and plotting firing pattern. We show that delay in the information transmission can induce fruitful synchronization transitions, including transition from phase locking to antiphase synchronization, and transition from antiphase synchronization to complete synchronization. Furthermore, the delay-induced complete synchronization can be changed by diversity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…For phase synchronization of burst neurons, it has been found that at a certain noise intensity the onsets of bursts in different neurons could become phase synchronized. 17 Moreover, some factors such as coupling strength, [26][27][28] coupling forms, 29 diversity, 30 noise, 31 and especially time delay [32][33][34][35] could induce various phase synchronization transitions in neuronal networks.…”
Section: Introductionmentioning
confidence: 99%
“…For phase synchronization of burst neurons, it has been found that at a certain noise intensity the onsets of bursts in different neurons could become phase synchronized. 17 Moreover, some factors such as coupling strength, [26][27][28] coupling forms, 29 diversity, 30 noise, 31 and especially time delay [32][33][34][35] could induce various phase synchronization transitions in neuronal networks.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, complex networks have attracted a lot of attention and various topologies of networks have been investigated in the nervous system [14,15,[22][23][24][25][26][27][28][29][30][31][32]. For example, the developing hippocampal networks in CA3 region exhibit a scale-free topology [51].…”
Section: Introductionmentioning
confidence: 99%
“…If time delay is introduced, synchronization can be achieved at smaller coupling strength [11][12][13]. A network can exhibit multiple synchronous behaviors that appear at time delay being of integer multiple to the intrinsic period of the individual neurons in the network [22][23][24][25][26][27][28]. Inhibitory synapses are widely spread in the nervous systems [19,[29][30][31][32] and can play important roles in the achievement of physiological functions such as encoding of spatial information and the formation of episodic memory [33].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been suggested that time delays between neurons can facilitate and stabilize the synchronization of neural networks [10][11][12][13], induce multiple stochastic resonances under noisy environment [14][15], and modulate the oscillatory activity of neuron assemblies [16][17]. Moreover, in some neuronal circuits with the connection type of scale-free [18][19] and small-world [20][21], synchronous activity can switch from one state to another with the variation of time delay. Notably, in hybrid neuronal networks of the entorhinal cortex, shorter conduction delays tend to stabilize the synchronization of neuronal network with inhibitory couplings rather than excitatory couplings [22].…”
Section: Introductionmentioning
confidence: 99%